Quadriceps Muscle Fatigue in Trained and Untrained Boys - Callewaert, M.; Boone, J.; Celie, B.; De Clercq, D.; Bourgois, J. (International Journal of Sports Medicine, 2013)
This study aimed to explore muscle oxygen extraction and muscle activation pattern during bilateral intermittent submaximal isometric knee-extensions by combining Near-infrared Spectroscopy (NIRS) and Electromyography (EMG) measurements from the M. Vastus Lateralis. A group of highly specifically trained boys (youth sailors) (n=10) and untrained matched controls (n=10) performed 12 bouts of 90 s bilateral submaximal (30–40% MVC) isometric knee-extension interspersed with 6 s recovery-periods. Patterns of deoxygenated haemoglobin and myoglobin concentration (Deoxy[Hb+Mb]) were observed during each bout and the entire protocol. Reoxygenation Index (RI) was assessed for each recovery period as the amplitude of Deoxy[Hb+Mb]-decrease relative to amplitude of Deoxy[Hb+Mb]-increase during each bout. Root Mean Square (RMS) and Mean Power Frequency (MPF) were calculated for each bout as an average of the final 60 s. Deoxy[Hb+Mb], RI, RMS and MPF were analyzed by repeated-measures ANOVA. Results indicated significantly higher Deoxy[Hb+Mb]-increase and lower RI in specifically trained boys compared to untrained controls. These differences are presumably related to the differences in EMG-measurements which demonstrated lower RMS-increase and MPF-decrease for trained compared to untrained boys. In conclusion, specifically trained boys indicate delayed onset of muscle fatigue in comparison to untrained controls, which might be associated with the different pattern of muscle O2-extraction or muscle activation pattern (i. e., a more accurate recruitment of slow-twitch fibres).
Keywords: NIRS; EMG; reoxygenation; isometric; knee-extension